Impact of PM2.5 exposure on depressive symptoms among elderly residents in China, 2018: a CHARLS data analysis - Yidi CHEN; Jilei WU (Zhongguo gonggong weisheng, 2024)
ObjectiveTo assess the effect of exposure to particulate matter less than 2.5 micrometers in aerodynamic diameter (PM2.5) on the prevalence of depressive symptoms in elderly people in China, to provide a reference for the prevention of symptoms in the population. MethodsData on 10 350 residents aged 60 years and older living in 124 prefecture-level cities across China during 2015 – 2018 were extracted from the China Health and Retirement Longitudinal Study (CHARLS) conducted in 2018, and city-specific data on air pollution and meteorology during the 4-year period were also collected simultaneously. The two-stage least squares regression model with instrumental variable method was used to analyze the effect of PM2.5 exposure on the prevalence of depressive symptoms assessed by the 10-item Center for Epidemiologic Studies Depression Scale (CESD-10) in the CHARLS survey among the elderly.ResultsOf all the elderly residents, 3 535 (34.15%) were assessed as having depressive symptoms. After adjusting for gender, age, education level, marital status, type of household registration, region of residence, chronic disease status, social participation, participation in health and pension insurance schemes, the logarithm of average gross domestic product, average annual temperature, and average annual precipitation, the results of instrumental variable method two-stage regression analysis showed that higher PM2.5 concentration was associated with increased prevalence of depressive symptoms among the elderly residents, with the odds ratios (95% confidence interval) of 1.02 (1.01 – 1.04) for current higher annual average PM2.5, 1.02 (1.01 – 1.03), 1.01 (1.00 – 1.02) for lagged one-, two-year higher annual average PM2.5 concentrations, and 1.41 (1.13 – 1.77) for continuous exposure to PM2.5 pollution (≥ 35 μg/m3). ConclusionThe prevalence of depressive symptoms is relatively high, and exposure to higher PM2.5 might increase the risk of depressive symptoms among elderly people in China.